An Extensionist’s Guide to Farm and Site Visits - Marcelo Wallau; Bob Hochmuth; Tatiana Sanchez-Jones; Mark Warren; Carissa Wickens; Prissy Fletcher; Cheryl Mackowiak (EDIS)
Farm and site visits are a major component of Extension work, whether as a county faculty or state specialist. They serve various purposes, such as informal check-ins, relationship-building, problem-solving, sharing technology, and information collection. While time-consuming, farm visits are often the most effective method for addressing problems and developing deeper connections with stakeholders (Petrzelka, Padgitt, and Windestenn, 1999). These visits provide firsthand knowledge of the issues clients face and are effective in establishing collaborations, assessing needs, understanding agricultural production systems, and validating research applications (Oakley and Garforth, 1985; Seevers and Graham, 2012). This publication explores different facets of farm and site visits, including preparation before the visit, the investigative (problem-solving) process during the visit, and post-visit procedures. Additional resources are included to support client visits and troubleshooting.